Investigation of Multiple Hole Grouting for Reducing Water Inrush Risk in Underground Engineering - Changde Yang; Ling Li; Ying Li; Yakuan Gao (Advances in Materials Science and Engineering)
Reinforcement with grout as an environmentally friendly technology has played a key role in underground coal mining. The risk of the water inrush into coal mines can all be reduced by grouting. A model that integrates a geographic information system (GIS), distribution of quantity of grouting injected, and water inflow correlation method is proposed here to evaluate the effects of grouted reinforcement in coal mining. The temporal and spatial characteristics of the volume of grout injected and water yield of aquifers are analyzed by using the GIS, and the rate of filling of cement slurry and its distribution characteristics are determined. The effects of grouting on the aquifers which has been carried out to reduce their permeability are determined by comparing the spatial temporal variations in the volume of the grout injected, water yield, and rate of filling of the cement slurry. The method was applied in a case study in a coalmine in Henan province, China, in which the risk of the water inrush from karst aquifers has been reduced by grouting. There are three limestone aquifers, namely, L8, L10, and L11 which underlie an exploitable coal seam. The result indicates that most of the cement slurry is consumed when the water yield is 20 to 30 m3/h; and that there are minimal changes of the electrical properties of the rock stratum under coal seam when the water yield of L11 is low within the range of 40 m. The resistivity of the aquifers before and after grouting and their spatial characteristics are tested by using the transient electromagnetic method (TEM), and this shows that there are no areas with low resistivity. The electrical properties of the strata at a depth that ranges from 40–80 m with transverse homogeneity show that Aquifers L10 and L11 have been transformed into aquicludes. The reinforcement effect of aquifers with grout is good.